Correction: Accuracy of Genomic Selection in a Rice Synthetic Population Developed for Recurrent Selection Breeding. - Cécile Grenier; Tuong-Vi Cao; Yolima Ospina; Constanza Quintero; Marc Henri Châtel; Joe Tohme; Brigitte Courtois; Nourollah Ahmadi (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0136594.].